Pengembangan Pariwisata Cerdas untuk Pelestarian Desa Wisata di Kabupaten Sumba Barat Daya: Pendekatan (UCD) - Gergorius Kopong Pati; Trisno Trisno (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Smart tourism development is an important strategy for strengthening the competitiveness of tourism villages while preserving local culture, environmental sustainability, and community life. Southwest Sumba Regency possesses natural and cultural tourism potential; however, its management faces limitations in information provision, digital promotion, community participation, and tourism services. This study aims to design a smart tourism development model to support the preservation of tourism villages in Southwest Sumba Regency using a User-Centered Design (UCD) approach. This approach places local communities, tourism village managers, tourists, local government, and business actors as users throughout the design process. The study employs a mixed-methods approach comprising field observation, interviews, focus group discussions, questionnaires, user-needs analysis, prototype development, and usability evaluation. The UCD stages include identifying the context of use, specifying user requirements, developing solutions, and conducting evaluations. The expected outcome is a smart tourism platform prototype that provides destination information, promotes local products, presents cultural event calendars, maps tourism locations, supports reservation services, and facilitates community participation. The study is also expected to produce a digital governance model grounded in cultural values, local wisdom, and sustainability principles. The targeted outputs include a system prototype, policy recommendations, a tourism village management model, and an article. The proposed model is expected to improve tourist experiences, expand market access, strengthen community capacity, and preserve tourism village identities sustainably. Technology is therefore positioned not merely as a promotional tool, but also as a means of documentation, education, decision-making, tourism impact monitoring, and inclusive, adaptive, and sustainable collaboration among stakeholders.